Perceptions and misperceptions of overdetection of breast cancer - Jansen, Jesse; Houssami, Nehmat (Translational Cancer Research, 2018)
In the rapidly progressive world of cancer research and discovery, concerns about overdetection, or overdiagnosis, whether relating to breast cancer or other types of cancer, seem remote and counterintuitive.